Mafeje's Search for Africanity. Issue 1 (2nd January 2022) - Nyoka, Bongani
Abstract: Archie Mafeje believes that intellectual liberation is a struggle worth fighting and that it is as legitimate as any other. Accordingly, African intellectuals have to make their mark and cease to be dominated by their Euro-American counterparts. Mafeje believes, too, that knowledge production is not only ideological, but also political. In his early work on epistemological and methodological issues in the social sciences, he allows his scholarship to lead his politics. Yet, in his later work on knowledge decolonisation as Africa's "second independence, " he allows his politics to lead his scholarship. Focusing on Mafeje's notion of Africanity, I discuss these issues in greater detail.